Economic Impact on Andalusian Economy of European Funds using a Dynamic Computable General Equilibrium Model: 2014-2020 - María del Carmen Delgado López; Manuel Alejandro Cardenete Flores; María del Carmen Lima Díaz (European Regional Science Association (ERSA), 2012)
This paper analyses the economic impact of the foreseeable withdrawal of a large amount of the European Structural funds in the Andalusian economy, for the 2014-2020 Community Support Framework. We develop a Dynamic General Equilibrium Model that will assess, under different simulation scenarios, the effects of the removal of this funding on the main regional economic indicators. This is the first time that Andalusia will not be considered as one of the Objective 1 priority areas for the European regional policy. The model analyzes the effect of economic policy actions on a particular economy, satisfying the requirements of welfare and technological feasibility and given some restrictions on available resources.
Keywords: C68; R11; R15; 330; applied general equilibrium models; European regional policy; Impact analysis